Method Validation and Characterization of Red Pigment in Beta vulgaris Peels and Pomaces by HPLC-UV and UHPLC-MS/MS - Vincent Rotich; Phanice Wangila; Jackson Cherutoi (Journal of Analytical Methods in Chemistry)
Color pigments from plant, animal, or mineral sources can be identified, separated, and quantified for various purposes. It is expected that pigments from Beta vulgaris L. peels and pomaces could be used to develop natural dyes that can find applications in areas such as food or textile dyeing industries. This work aimed at identifying and quantifying the pigment in the B. vulgaris L. peels and pomaces extracts as well as validating the method by high-performance liquid chromatography combined with ultraviolet spectroscopy (HPLC-UV) and ultra-high-performance liquid chromatography coupled with triple quadrupole (TSQ) mass spectrometry (UHPLC-MS/MS). Column chromatography was used to isolate compounds after methanolic solvent extraction. Identification and quantification of the pigments in the extract were achieved using reverse-phase HPLC with a UV detector (538 nm). The UHPLC-MS/MS was used for further confirmation of colored compounds in the extract. Method validation included the use of betanin standard (betanidin 5-β-D-glucopyranoside), determination of repeatability (precision), calibration curve linearity, and sensitivity (LOD and LOQ) tests. Betanin was detected in the sample at retention times of 7.699 and 7.71 minutes, respectively, which closely matched the tR (7.60 min) of the standard, according to HPLC-UV and LC-MS/MS data. The average betanin concentration was 3.81 0.31 mg/g of dry weight, according to the HPLC-UV analysis. The LC-MS/MS data revealed the existence of several compounds, including betanin (4.31 ± 2.15 mg/g), isobetanin (1.85 ± 2.20 mg/g), 2, 17-bidecarboxy-neobetanin (0.71 ± 0.02 mg/g), betanidin (0.71 ± 0.03 mg/g), 2-O-glucosyl-betanin (0.40 ± 0.10 mg/g), and isobetanidin (0.36 ± 1.26 mg/g), among other compounds whose yields were too low. In conclusion, the peels and pomaces of B. vulgaris L. can be a useful source for the extraction of a red dye for use in coloring, such as the dyeing of textile substrates.